Towards a new transition economics. Issue 1 (6th December 2012) - Pistor, Katharina
Abstract In these brief comments, I take issue with the thesis expressed in Konstantin Sonin's conference review that economic transition is a thing of the past. To the contrary, I argue that it has only just begun, and so has the process of rethinking the economic theories and models that have framed the subfield of transition economics. Specifically, I point out that the many surprises economists have encountered when confronted with the actual results of the transition process reveal deep flaws in the analytical framework that informs their analyses and policy prescriptions. If protecting existing theories and models is of primary importance, we should indeed call an end to economic transition and the subfield it has engendered. If, however, the issue is to understand real economies and their dynamic change over time and to improve the results of contemporary and future reform efforts there is a strong case for a New Transition Economics.